Implications of Hazairin and Munawir Sjadzali Thoughts In Establishment of Islamic Inheritance In Indonesia - Sugiri Permana (Universitas Islam Negeri Jakarta, 2018)
Inheritance law is one of islamic law that always dinamically follow the time. The history showed when abu bakr period, two years after the death of prophet, has renewed inheritance law. Indonesias became an important part of inheritace law. This development isnt regardless from the thinker and scholar in indonesia. Among scholar who have a great influence on inheritance law in indonesia are hazarin and munawir sjadzali. both of figures are famous for their controversy. Hazarin famous for the thought the equality of between grandchildren male and female. while sjadzali famous her thought the equality between man and women. hazarin tend to think that is still near to the nash alquran, while munawir to deviates from nash provisions. In its development, the development of hazarin was adopted by inherentance law in Indonesia. the compilation of islam law has decided the existence of substitute heird in which one of them comes from the thought on Hazarin who positioned equally between granddaughter and grandson.